Epidemiology of fractures during COVID-19 pandemic: a short review - Nowaczek, Justyna; Oszczędłowski, Paweł; Pytka, Michalina; Giermasiński, Adrian (Journal of Education, Health and Sport, 2021)
Summary Introduction and purpose: The purpose od this study is to describe changes in epidemiological trends of fractures, especially osteoporotic fractures, during COVID-19 pandemic. Before the pandemic, fractures in the young population were more frequent than in elderly population, because of more active lifestyle. A brief description of the state of knowledge: COVID-19 pandemic and lockdown has effectively reduced people’s mobility and ability to travel. This has resulted in lowered rate of traumatogenic incidents that cause fractures, including traffic accidents and accidents during performing sport. When people spend more time at their homes, incidence of household fractures is growing, especially in elderly population. Osteoporosis makes bones of elderly people more suspectible to fracture. Majority of drugs used in treatmen for osteoporosis are said not to interact with risk or severity of COVID-19 infection. Conclusions: During the COVID-19 pandemic, geriatric fractures have become one of the severe problems for healthcare systems. Isolation at people’s homes has resulted in increased rate of fractures occuring at home, especially in elderly population. Difficulties caused by pandemic made rates of properly performed osteoporotic treatment lower, increasing risk of fractures even more. Mortality after fractures has risen even in patients with negative result of testing for COVID-19.